2008
DOI: 10.1111/j.1365-2850.2007.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health professionals' attitudes towards consumer participation in inpatient units

Abstract: Consumer participation has been a major focus in mental health services in recent years, but the attitudes of mental health professionals towards this initiative remain variable. The purpose of this study was to describe mental health professionals' attitudes towards mental health consumer participation in inpatient psychiatric units. The Consumer Participation and Consultant Questionnaire was used with a non-probability sample of 47 mental health professionals from two adult inpatient psychiatric units situat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 22 publications
1
58
0
1
Order By: Relevance
“…The literature emphasises the negative and stigmatising attitudes of mental health professionals towards people diagnosed with a mental illness (Bertram & Stickley, 2005;Bluebird, 2004;Cowling et al, 2006;Crawford & Rutter, 2004;Goodwin & Happell, 2006, 2007a, 2008Lammers & Happell, 2003;McAllister & Walsh, 2004;McCann et al, 2008;Middleton et al, 2004;Petersen et al, 2008). In the current study the nursing student participants appear to be very supportive of the active engagement of consumers in relation to the mental health services they receive.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The literature emphasises the negative and stigmatising attitudes of mental health professionals towards people diagnosed with a mental illness (Bertram & Stickley, 2005;Bluebird, 2004;Cowling et al, 2006;Crawford & Rutter, 2004;Goodwin & Happell, 2006, 2007a, 2008Lammers & Happell, 2003;McAllister & Walsh, 2004;McCann et al, 2008;Middleton et al, 2004;Petersen et al, 2008). In the current study the nursing student participants appear to be very supportive of the active engagement of consumers in relation to the mental health services they receive.…”
Section: Discussionmentioning
confidence: 49%
“…The attitudes of mental health professionals have been identified as a major barrier to facilitating the change in prac-tice required to ensure that consumer participation moves beyond rhetoric to become reality (Bertram & Stickley, 2005;Bluebird, 2004;Cowling, Edan, Cuff, Armitage, & Herszberg, 2006;Crawford & Rutter, 2004;Goodwin & Happell, 2006, 2007a, 2008Lammers & Happell, 2003;McAllister & Walsh, 2004;McCann, Baird, Clark, & Lu, 2008;Middleton, Stanton, & Renouf, 2004;Petersen, Hounsgaard, & Nielsen, 2008). Consumer participation challenges the traditional power base of the health professional which gives preference to the clinical voice and the assumption that he or she knows what is in the best interests of the consumer.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…There have been a few studies that have examined staff and professional attitudes to community, consumer or lay participation in specific organizational contexts and processes 22,27–30 . Surveys conducted in Australian drug treatment and mental health services have found positive staff attitudes to consumer participation 31,32 . Another Australian survey found staff attitudes become more positive over time and as a direct result of interaction with community members in health care decision‐making forums 30 .…”
Section: Introductionmentioning
confidence: 99%
“…An Australian study of demographic and workforce characteristics and their relationship to acceptance of peer providers found that receptivity and support for consumer involvement in treatment-related activities varied by gender (females more supportive), time in the profession (junior people more receptive), and time in the job (most senior and most junior least receptive). 134 …”
Section: A Green Et Almentioning
confidence: 99%